Case Study - Bayport Financial Services : How Can Businesses Tap Local Capital Markets to Expand? - Shi, Lin (International Finance Corporation, Washington, DC, 2018)
Bond markets, though still underdeveloped in Africa, are beginning to emerge as a realistic financing option for private companies looking to invest or expand their operations on the continent. Multilateral development banks can play a critical role in that process by issuing bonds in local currencies and providing risk guarantees and anchor investments to companies looking to issue their own bonds.